COMPARISON OF INJURY PREVENTION PROGRAM ON PHYSICAL FITNESS AMONG CRICKETERS IN WARM-UP AND COOL-DOWN PHASES - Muhammad Faheem Afzal; Amna Imran Raha; Adeela Arif; Aamir Gul Memon; Khurrum Sarfraz; Hafiz Muhammad Waseem Javaid Shalamar (The Rehabilitation Journal, 2021)
Background: Cricket is considered 2nd most famous sports while the chances of injuries are very high. Proper warm-up, cool down exercises play important role in reduction of injuries and cricket injury prevention program may be effective in warm-up or cool-down phases of training. Objective: To compare the effects of injury prevention program on physical fitness among cricketers in warm-up and cool-down phases. Methods: A Randomized Clinical Trial (NCT04017715) was conducted at Rawalpindi cricket club. Subjects were recruited through purposive sampling. The inclusion criteria were athletes registered with Pakistan Cricket Board, age 16-30 years and attending minimum 3 sessions were week. The n=55 subjects were recruited and randomly divided into three groups by sealed and envelop method. Cricket Injury Prevention Program introduced in warm-up and cool-down phases in Group A (n=18) and B (n=20) respectively and group C (n=17) is considered as control group for 6 weeks. Assessment were taken through 100m sprint, Burpee test, Illinois Agility Run test, plank test and star excursion balance test at baseline and after 6 weeks of intervention. Data analysis was done through SPSS 25. Results: The mean age of the subjects was 19.31±2.79, mean Body Mass Index was 18.77±1.58. There is a significant difference among all groups in 100m sprint, T agility, plank test, 3 minutes burpee test and start excursion test (p value˂0.05).Conclusion: Cricket injury prevention program (CIPP) is effective in preventing injuries in cricketers in both warm up and cool down.